2022
DOI: 10.3390/neurosci3030027
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Neurocognitive Performance of Memory, Attention, and Executive Function

Abstract: Background: Obesity has been linked to an increased risk of dementia in the future. Obesity is known to affect core neural structures, such as the hippocampus, and frontotemporal parts of the brain, and is linked to memory, attention, and executive function decline. The overwhelming majority of the data, however, comes from high-income countries. In undeveloped countries, there is little evidence of a link between obesity and neurocognition. The aim of this study was to investigate the effects of BMI on the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…These problems could decrease the students’ abilities and therefore academic achievement. Additionally, a recent study found that obese persons had lowered cognitive performance on tasks involving memory, attention, and executive function [23]. This result is different from another study that showed that obesity did not influence academic performance among students from the College of Science and College of Medicine of Imam Mohammad Ibn Saud Islamic University in Saudi Arabia [24].…”
Section: Discussionmentioning
confidence: 92%
“…These problems could decrease the students’ abilities and therefore academic achievement. Additionally, a recent study found that obese persons had lowered cognitive performance on tasks involving memory, attention, and executive function [23]. This result is different from another study that showed that obesity did not influence academic performance among students from the College of Science and College of Medicine of Imam Mohammad Ibn Saud Islamic University in Saudi Arabia [24].…”
Section: Discussionmentioning
confidence: 92%
“…Also, since obesity is often associated with sleep apnea and other sleep disorders, it can cause daytime sleepiness and further impair cognitive functions. 44 Another possible explanation is that individuals with obesity may experience greater levels of stress and anxiety. This can affect attention and concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since obesity is often associated with sleep apnea and other sleep disorders, it can cause daytime sleepiness and further impair cognitive functions. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obesity leads to chronic low-grade systemic inflammation, which potentially causes neuroinflammation [ 47 ]. In particular, obesity increases levels of circulating free fatty acids, immune cells, and pro-inflammatory cytokines, which enhance blood–brain barrier permeability and ultimately enter the hypothalamus [ 47 , 48 , 49 ]. This leads to activation of the pro-inflammatory transcription factor NF-κB and the increased expression of pro-inflammatory mediators and cytokines, resulting in the development of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%